Teen Relationship Abuse Research Study - Donna Davis (EDIS, 2012)
“When we think of violence between intimate partners, we often think of domestic abuse between adult men and women, and most often between husbands and wives. However, in a recent study commissioned by Liz Claiborne Inc., researchers discovered deep and troubling evidence that today’s teens are not only experiencing dating violence, but are accepting it as normal.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.